A Pilot Study on Extending the SUS Survey: Early Results. (September 2021) - Harper, Samantha B.; Dorton, Stephen L.
The System Usability Scale (SUS) is a popular method to measure the subjective usability of a system, due largely to the simplicity and rapidity of both collecting and analyzing data. A drawback is that the SUS generates a single unidimensional usability score from 0-100. Several researchers have amassed larger datasets across multiple projects to allow for analysis on additional methods to glean insights from the SUS survey. Along these lines, we investigate the practical value of extending the SUS survey with additional items such as open text responses, and test underlying assumptions of how SUS results are interpreted. We found that while a lower SUS score does generally correlate to a stronger desire to modify the system, people generally want to make modifications to a system regardless of its usability. Further, we found that the amount of user feedback related to modifications to a system provided predicted subjective usability ratings.